Pollen-Specific Aquaporins NIP4;1 and NIP4;2 Are Required for Pollen Development and Pollination in Arabidopsis thaliana - Di Giorgio, Juliana Andrea Pérez (Plant Cell, 2016)
In flowers with dry stigmas, pollen development, pollination, and pollen tube growth require spatial and temporal regulation of water and nutrient transport. To better understand the molecular mechanisms involved in reproductive processes, we characterized NIP4;1 and NIP4;2, two pollen-specific aquaporins of Arabidopsis thaliana. NIP4;1 and NIP4;2 are paralogs found exclusively in the angiosperm lineage. Although they have 84% amino acid identity, they displayed different expression patterns. NIP4;1 has low expression levels in mature pollen, while NIP4;2 expression peaks during pollen tube growth. Additionally, NIP4;1(pro):GUS flowers showed GUS activity in mature pollen and pollen tubes, whereas NIP4;2(pro):GUS flowers only in pollen tubes. Single T-DNA mutants and double artificial microRNA knockdowns had fewer seeds per silique and reduced pollen germination and pollen tube length. Transport assays in oocytes showed NIP4;1 and NIP4;2 function as water and nonionic channels. We also found that NIP4;1 and NIP4;2 C termini are phosphorylated by a pollen-specific CPK that modifies their water permeability. Survival assays in yeast indicated that NIP4;1 also transports ammonia, urea, boric acid, and H(2)O(2). Thus, we propose that aquaporins NIP4;1 and NIP4;2 are exclusive components of the reproductive apparatus of angiosperms with partially redundant roles in pollen development and pollination.